Tumor‐Responsive Small Molecule Self‐Assembled Nanosystem for Simultaneous Fluorescence Imaging and Chemotherapy of Lung Cancer. (28th October 2016) - Yang, Yuming; Yue, Caixia; Han, Yu; Zhang, Wei; He, Aina; Zhang, Chunlei; Yin, Ting; Zhang, Qian; Zhang, Jingjing; Yang, Yao; Ni, Jian; Sun, Jielin; et al.
Abstract : Cancer therapeutic drugs face various transportation barriers in transit to the tumor site, making the delivery of effective drug concentrations problematic. Moreover, these drugs are very difficult to use due to their adverse off‐target effects. Thus, it is very essential to develop a drug delivery system that can deliver drugs to achieve effective local concentrations without side effects on healthy tissues. Herein, the authors report a self‐assembled nanodrug system in which hydrophobic antitumor drugs are packaged into nanoparticles to improve water solubility, tumor targeting ability, blood retention time, and chemotherapeutic effect. The nanodrugs are degraded into smaller ones when exposed to the tumor microenvironment, extravasated from leaky regions of the tumor vasculature, and displayed matrix metalloproteinase‐2 (MMP‐2)‐induced degradation and antitumor property. To construct this unique system, an amphiphilic multifunctional molecule (Pep‐Cy5) is synthesized by attaching a MMP‐2‐cleavable peptide to a hydrophobic near‐infrared dye, Cy5. Two hydrophobic anticancer drugs are conjugated to Pep‐Cy5 through hydrophobic interactions to form the self‐assembled nanodrug system. The MMP‐2‐induced degradation and hydrophobic antitumor drug interchangeability features of this nanosystem enable the hydrophobic antitumor drugs to exhibit longer blood‐retention times, improved intratumoral accumulation, fewer side effects, and higher anticancer efficacies compared with free drugs. Abstract : Schematic illustration of self‐assembly, matrix metalloproteinase‐2‐induced degradation process for the self‐assemble nanodrugs . The hydrophobic antitumor drugs self‐assembled into water‐soluble nanoparticles through hydrophobic interactions with Pep‐Cy5. The blue ball represents the self‐assembled nanodrugs. The brown ball represents tumor tissue. The nanodrugs degrade into small particles, which readily diffuse throughout the tumor's interstitial space.